Widefield swept source optical coherence tomography for the monitoring of choroidal infiltrates - Mariana Vaz; João Salgueiro; Pedro Carreira; Margarida Brízido; Daniel Lopes; Diogo Cabral (American Journal of Ophthalmology Case Reports)
Choroidal Infiltrates (Cis) detection is traditionally done using invasive imaging. We herein report the usage of topographic choroidal thickness maps (ChT maps) and en face swept-source Optical Coherence Tomography (OCT) as a rapid and non-invasive technique to monitor Cis in a patient with Chronic Lymphocytic Leukemia.